Cognitive Load Theory and the Teaching of Complex Concepts in Senior Secondary School Chemistry Curriculum: The Place of Element Interactivity - Agwu, Christopher Okechikwu; Arokoyu, Abosede Ajoke. (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
In the effort to develop a procedural guide for teachers on effective delivery of instructional contents, this study used a conventional lesson note on electrolysis for SS2 Chemistry students to derive examples of the facts, concepts, processes, procedures and principles of learning matter, being the content type elements of knowledge embedded in the concept of electrolysis. These elements were used to explain the interactions that take place amongst the elements of a complex learning matter. The study also highlighted the components of cognitive load which arise to hinder or facilitate meaning making, based on the level of interactivity of the elements and the background knowledge of a learner. To achieve the objectives of instruction, teachers are encouraged to ensure that learners comprehend the interacting elements of learning matter individually before presenting chunks of same for the achievement of the target learning outcomes.